(Invited) A Sub-1G MEMS Sensor. (27th March 2015) - Yamane, Daisuke; Konishi, Toshifumi; Toshiyoshi, Hiroshi; Masu, Kazuya; Machida, Katsuyuki
Abstract : This paper presents our recent research progress of highly-sensitive micro-electro-mechanical systems (MEMS) capacitive accelerometers for monitoring micro motion and vibration at the acceleration scale of lower than 1 G (G = 9.8 m/s 2 : gravitational acceleration). To reduce the Brownian noise ( BN ) on the sensors, we have employed high-density metal for proof mass, and implemented the MEMS structures. Proof-of-concept inertial sensors have been developed by gold electroplating, and we have estimated the BN to be below 10 μG/Hz 1/2, which is nearly one order of magnitude smaller than those of the conventional MEMS accelerometers with the same proof mass size. The experimental results indicate that the proposed sensor concept would be a promising way to further improve the sensitivity and miniaturization of micro-scale motion sensors, which could advance the emergence of new MEMS applications.